基于SKETCH ENGINE的汉语近义词辨析研究 - Diana Constansz Sahertian (Fakultas Sastra Universitas Darma Persada, 2023)
Abstract This study aims to describe the similarities and differences in collocation behavior and semantic preferences between two synonymous Chinese verbs, hulüe (忽略) and hushi (忽视). The data derives from the Chinese Web 2017 (zhTenTen11) Simplified corpus in Sketch Engine. This study applies both quantitative and qualitative methodologies. The results of the research show that both synonymous words often collocate with abstract nouns, adverbs, verbs, adjectives and prepositions (“zai在”, “gei给”, “cong从”, “yu与”, “dui对”, “bei被”, “ba把”, “jiang将”). Some of them only collocate with “hulüe” or “hushi”, some collocate with both “hulüe” and “hushi”, but according to the frequency of occurrence, some tend to co-occur with one of them. Referring to Ucrel Semantic Analysis System, nouns classified in the